Corporate governance and firm performance in Malaysia / Siti Noorazliena Anuar - Anuar, Siti Noorazliena (2022)
This article studies the influence of corporate governance codes and standards on the performance of organizations listed on the Bursa Malaysia. In today's complicated global business world, the association between corporate governance and firm success has received a lot of attention. Businesses must be able to browse transnational pools of cash as well as attract qualified human capital from across the world. In such a circumstance, a firm will be unable to flourish unless their values and exhibits ethical behaviour. The goal of this research is to investigate the relationship between corporate governance and firm performance. From 2011 to 2020, the 8 leading listed businesses in the consumer product and services category on the Bursa Malaysia were subjected to quantitative research using criteria.